A Guided Tour of the Structural Biology of Gaucher Disease: Acid-β-Glucosidase and Saposin C. (21st September 2011) - Lieberman, Raquel L.
Abstract : Mutations in both acid- β -glucosidase (GCase) and saposin C lead to Gaucher disease, the most common lysosomal storage disorder. The past several years have seen an explosion of structural and biochemical information for these proteins, which have provided new insight into the biology and pathogenesis of Gaucher disease, as well as opportunities for new therapeutic directions. Nearly 20 crystal structures of GCase are now available, from different heterologous sources, complexed with different ligands in the active site, in different glycosylation states, as well as one that harbors a prevalent disease-causing mutation, N370S. For saposin C, two NMR and 3 crystal structures have been solved, each with its unique snapshot. This review focuses on the details of these structures to highlight salient common and disparate features that contribute to our current state of knowledge of this complex orphan disease.